The Effect of Vine Spacing on Some Physiological Aspects of Vitis vinifera L. (cv. Pinot noir) - Archer, E.; Strauss, H.C. (South African Journal of Enology and Viticulture, 2017)
The effect of vine spacing on leaf temperature, radiant energy, some canopy characteristics, leaf-water potential, stomata! conductance, the rate of transpiration and the rate of photosynthesis was measured and discussed. With more closely spaced vines, canopies were less dense than with more widely spaced vines mainly because of less vigorous shoot growth. The consequent better sunlight penetration favoured the physiology of more closely spaced vines early in the season. During the latter part of the season the situation was reversed and the physiology of more widely spaced vines was favoured mainly because of better water supply.